(untitled) (مجلة أبحاث قانونية, 2023)
The study began by clarifying the concept of the disciplinary system and its basic elements, represented in: the violation of the disciplinary system, the disciplinary sanction, legal procedures, the disciplinary authority, and the administrative investigation that requires research Studying and ascertaining the nature of the object subject of the violation, and the guarantees on which it depends is governed and regulated by legal procedures and rules that preserve the freedoms and rights of all its parties: the public servant, the competent authority, and the public of beneficiaries. The study then moved to explain the relationship between the role of the disciplinary system and administrative corruption: material, moral, explaining the importance of using this system as an economic and social mechanism, leading to raising the level of performance of the public employee, Increasing the efficiency of the State’s administrative apparatus, thereby increasing its capacity to provide the needs of society for goods and services, which leads to economic and social progress.